Canine and feline endocrinology - Feldman, Edward C.; Reusch, Claudia; Scott-Moncrieff, J. Catharine R.; Nelson, Richard William (Elsevier Saunders, 2015)
No other title offers such dedication to the depth, experience, and focus of endocrinology as Canine and Feline Endocrinology, 4th Edition. Comprehensive coverage includes virtually every common and uncommon condition in endocrinology, plus the most updated information on nutrition, geriatric care, pathophysiology, testing procedures, and cost-effective and expedient diagnostic protocols. With its logical, step-by-step guidance for decision making, diagnosis, and prescribing, you will be well-equipped to care for the wide spectrum of endocrine and metabolic disorders in dogs and cats
Includes bibliographical references and index. - Preceded by Canine and feline endocrinology and reproduction / Edward C. Feldman, Richard W. Nelson. 3rd ed. c2004
Weitere Ausgabe: Print version --->: Canine and feline endocrinology
Keywords: CatsxEndocrinology; CatsxDiseases; DogsxReproduction; CatsxReproduction; DogsxEndocrinology; DogsxDiseases; Endocrine System Diseasesxveterinary; Cat Diseases; Genital Diseases, Femalexveterinary; Genital Diseases, Malexveterinary; Dog Diseases; Electronic books